The Effects of Consumer Behavior in Purchasing Tea in Selected Milk Tea Shops in Bagong Silang, Caloocan City: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Since the late 1980s, milk tea has been circulating. It is well-known in Taiwan since tea drinking was formerly a common activity in East Asia and remains so now. Inquirer.net (2020) published an advertisement ranking the Philippines second among Southeast Asian nations with the most bubble tea consumers. It is generally known among Filipinos that a milk tea craze began in 2011 and continues to this day. According to one report by Mdpi.com (2021), milk tea has been frequently drunk in the Philippines since 2011. Despite the success of the milk tea sector in the Philippines and increasing rivalry in the same industry, there are still customers who are hesitant to purchase milk tea, and there is an underlying cause for this behaviour. These factors determine whether Milk Tea will be a successful or failed company. The 4Ps of marketing assist businesses in promoting their products; however, not all businesses, particularly milk tea enterprises, understand how it functions and its effects. As a result, the researchers devised this study to determine the elements influencing consumer behaviour while purchasing milk tea at milk tea stores, assisting future companies in learning more about their customers. The study used a survey questionnaire to gather the data needed from 100 respondents who are purchasing in selected milk tea shops, including Bubble Tea Shop, Murachi Milk Tea Shop, and Wicked Cup Milk Tea Shop in Bagong Silang, and uses the convenience sampling method, a form of non-probability sampling which researcher chooses members merely based on proximity and does not consider whether representing the entire population or not. Most respondents are female, aged between 15 and 25 years old, currently students, with some having ₱9,520 below monthly income. Price, place, product, and people are variables associated with assessing the marketing mix using the 4Ps in purchasing, which are extremely effective in consumer behaviour. Personal factors, social factors, psychological factors, and cultural factors are variables associated with the factors influencing consumer behaviour that are extremely effective consumer behaviour. The study also shows no significant difference between the respondents' assessments of the marketing mix using the 4Ps in purchasing and factors influencing consumer behaviour; the biggest challenge encountered by the respondents in purchasing milk tea is overcharging the price of tea.
Keywords: Milk Tea; Marketing Mix; Consumer Behavior